Π-System based coordination polymer hollow nanospheres for the selective sensing of aromatic nitro explosive compounds. (28th September 2015) - Shi, Naien; Zhang, Yang; Xu, Dandan; Song, Chuanyuan; Jin, Xiaolei; Liu, Dong; Xie, Linghai; Huang, Wei
Abstract : π-System embedded coordination polymer hollow nanospheres were synthesized, which showed a good sensing performance for the detection of aromatic explosive nitro-compounds. Abstract : Herein, a type of π-system based fluorescent coordination polymer hollow nanospheres of terbium 1, 3, 5-benzenetrisbenzolate (TbBTB) was synthesized through a solvothermal process, and the nanospheres exhibited a good sensing performance for the detection of explosive aromatic nitro-compounds, as compared to aliphatic nitro-compounds as well as the small organic solvent molecules of dimethyl sulfoxide, chloroform and tetrahydrofuran. FESEM and TEM results showed that the spheres are 300–600 nanometers in diameter and they are composed of small nanoparticles of coordination polymer. The formation of the spheres is driven by the Ostwald ripening process under solvothermal conditions according to a series of corresponding control experiments. The sensing of aromatic nitro explosives may benefit from the special features of the nanospheres, which possess an intrinsic π-system of both π-conjugated ligands and intermolecular π–π stacking interactions, as well as their multiscale-porosity. This study may benefit the screening or design of fluorescent sensors for aromatic and aliphatic explosive nitro-compounds.